Enhancing Environmental Literacy Using EMKONTAN Learning for Biology Teacher Candidates - N. Nurwidodo; Sri Wahyuni; Iin Hindun (IKIP Mataram, 2023)
This study aims to analyze the effectiveness of the EMKONTAN learning model in improving environmental literacy for prospective biology teacher students. EMKONTAN is a student-centered learning model (students active learning), oriented to creative learning, problem-based learning, collaborative learning and provides opportunities for students to improve environmental literacy. This research was conducted in the event semester of the 2020/2021 academic year at IKIP Budi Utomo Malang (IBU) and FTTE Universitas Muhammadiyah Malang (UMM), involving 150 second semester students through total sampling. Data obtained through observation, questionnaires and tests. The research used a pretest-posttest non-equivalent control group design. The experiment was conducted from March to July 2021. Data collection in this study was carried out using Google Form, Google Classroom, Google Meet, and WhatsApp. Data analysis using SPSS software version 23. The ANCOVA analysis results showed that EMKONTAN, PBL affected students' creativity, collaboration skill and environmental literacy on biology teachers candidate students with a value of p<0.005. The LSD result was significantly different in improving students' environmental literacy. The EMKONTAN class gained the highest posttest score. Therefore, EMKONTAN could be applicable to improve environmental literacy outcomes in environmental learning.